Molecular simulation of copper based metal-organic framework (Cu-MOF) for hydrogen adsorption - Srivastava, Shashwat; Shet, Sachin P.; Priya, S. Shanmuga; Sudhakar, Kumarasamy; Tahir, Muhammad Suleman (Elsevier Ltd, 2022)
Metal organic framework (MOF) are widely used in adsorption and separation due to their porous nature, high surface area, structural diversity and lower crystal density. Due to their exceptional thermal and chemical stability, Cu-based MOF are considered excellent hydrogen storage materials in the world of MOFs. Efforts to assess the effectiveness of hydrogen storage in MOFs with molecular simulation and theoretical modeling are crucial in identifying the most promising materials before extensive experiments are undertaken. In the current work, hydrogen adsorption in four copper MOFs namely, MOF-199, MOF 399, PCN-6′, and PCN-20 has been analyzed. These MOFs have a similar secondary building unit (SBU) structure, i.e., twisted boracite (tbo) topology. The Grand Canonical Monte Carlo (GCMC) simulation was carried at room temperature (298 K) as well as at cryogenic temperature (77 K) and pressures ranging from 0 to 1 bar and 0–50 bar. These temperatures and pressure were selected to comply with the conditions set by department of energy (DOE) and to perform a comparative study on hydrogen adsorption at two different temperatures. The adsorption isotherm, isosteric heat, and the adsorption sites were analyzed in all the MOFs. The findings revealed that isosteric heat influenced hydrogen uptake at low pressures, while at high pressures, porosity and surface area affected hydrogen storage capacity. PCN-6′ is considered viable material at 298 K and 77 K due to its high hydrogen uptake.